2017
DOI: 10.1155/2017/5049802
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Atrial Fibrillation in the Course of Acute Pulmonary Embolism: Clinical Significance and Impact on Prognosis

Abstract: The relationship and clinical implications of atrial fibrillation (AF) in acute pulmonary embolism (PE) are poorly investigated. We aimed to analyze clinical characteristics and prognosis in PE patients with paroxysmal AF episode. Methods. From the 391 patients with PE 31 subjects with paroxysmal AF were selected. This group was compared with patients with PE and sinus rhythm (SR) and 32 patients with PE and permanent AF. Results. Paroxysmal AF patients were the oldest. Concomitant DVT varies between groups: p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 23 publications
1
14
0
2
Order By: Relevance
“…In a study by Kukla et al [26], RHT was found in 5% of the whole study group, in 8% of patients with paroxysmal AF, and in 7% of patients with nonparoxysmal AF [26]. In a study by Krajewska et al [3], the presence of RHT was confirmed in 5.9% of patients in sinus rhythm, with a tendency to a higher prevalence in the groups with paroxysmal AF and permanent AF (10% and 14.3%, respectively). The differences did not reach significance, mainly because of a small population size in both studies.…”
Section: Epidemiological Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Kukla et al [26], RHT was found in 5% of the whole study group, in 8% of patients with paroxysmal AF, and in 7% of patients with nonparoxysmal AF [26]. In a study by Krajewska et al [3], the presence of RHT was confirmed in 5.9% of patients in sinus rhythm, with a tendency to a higher prevalence in the groups with paroxysmal AF and permanent AF (10% and 14.3%, respectively). The differences did not reach significance, mainly because of a small population size in both studies.…”
Section: Epidemiological Datamentioning
confidence: 99%
“…Large-scale population-based studies have provided a considerable body of evidence on the involvement of PE in the onset of subsequent AF [3, 9, 30]. The increased risk of late-onset AF has been observed in patients after acute PE during long-term follow-up [24].…”
Section: Atrial Fibrillation As a Consequence Of Pulmonary Embolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of causation between PE and AF with slow ventricular response remains to be vague in the literature in which the exact pathophysiology and causal mechanism is yet to be fully understood [2, 3]. On a pathophysiological level that might demonstrate AF, Flegel concluded that a PE may trigger AF by causing acute right ventricular dilatation with strain, something that was evident in our case [4].…”
Section: Discussionmentioning
confidence: 72%
“…One of these rare complications are arrythmias such as atrial fibrillation (AF) [1]. Although rare, the ensuing presentation of AF secondary to PE is evident in the literature, however there has been no report of PE causing AF with slow ventricular response requiring a pacemaker [13]. We present a case of AF with slow ventricular response caused by a bilateral PE, with a conceivable pathophysiological hypothesis.…”
Section: Introductionmentioning
confidence: 99%